NBN Chemicals - Panlilio, Nora Monina H.P (College of Engineering, 1976)
Capacity: 2000 metric tons/year -- Land area: 1.5 hectares -- Fixed capital investment: P 18,350,000 -- Total product cost at maximum production: P 13,600,000 -- Sales at maximum production: P 20,000,000 -- Pay-off time: 2 years -- Break-even point: 340 metric tons/year